Performance of Geosynthetics Reinforced Subgrade Subjected to Repeated Vehicle Loads: Experimental and Numerical Studies - Hegde, Amarnath M.; Palsule, Prasad S. (Frontiers in Built Environment, 2020)
Use of the geosynthetics to strengthen the soil is one of the highly desirable techniques under static and dynamic loads. The present study describes the experimental and numerical studies performed on the geosynthetic reinforced subgrade subjected to repeated vehicle loads. The cyclic plate load tests were conducted on the sand subgrade reinforced with planar and 3D geosynthetic reinforcements. The vehicle load was simulated by applying a repeated load of magnitude 275 kPa with 1Hz frequency on the reinforced subgrade. Results of the experimental investigations revealed that the performance of the subgrade soil improved significantly in the presence of reinforcements. The estimated parameters illustrated the three-fold reduction in settlement of the subgrade in the presence of reinforcement. Further, the heaving of the subgrade soil was found completely arrested with the use of geosynthetic reinforcement. The three-dimensional geocell reinforcement performed effectively as compared to planar geogrids under dynamic load. The measured pressure values at different depth demonstrated a significant reduction in the pressure in the presence of reinforcements. Besides, numerical simulations were performed using PLAXIS2D to understand pressure and settlement distribution patterns in the reinforced subgrade. In overall, a good agreement was observed between numerical and experimental results.